The Regulation of Chemerin and CMKLR1 Genes Expression by TNF-α, Adiponectin, and Chemerin Analog in Bovine Differentiated Adipocytes - Suzuki, Y. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
Adipokines, adipocyte-derived protein, have important roles in various kinds of physiology including energy homeostasis. Chemerin, one of adipocyte-derived adipokines, is highly expressed in differentiated adipocytes and is known to induce macrophage chemotaxis and glucose intolerance. The objective of the present study was to investigate the changes of chemerin and the chemokine-like-receptor 1 (CMKLR1) gene expression levels during differentiation of the bovine adipocyte and in differentiated adipocytes treated with tumor necrosis factor-α (TNF-α), adiponectin, leptin, and chemerin (peptide analog). The expression levels of the chemerin gene increased at d 6 and 12 of the differentiation period accompanied by increased cytoplasm lipid droplets. From d 6 onward, peroxisome proliferator-activated receptor-γ2 (PPAR-γ2) gene expression levels were significantly higher than that of d 0 and 3. In contrast, CMKLR1 expression levels decreased at the end of the differentiation period. In fully differentiated adipocytes (i.e. at d 12), the treatment of TNF-α and adiponectin upregulated both chemerin and CMKLR1 gene expression levels, although leptin did not show such effects. Moreover, chemerin analog treatment was shown to upregulate chemerin gene expression levels regardless of doses. These results suggest that the expression of chemerin in bovine adipocyte might be regulated by chemerin itself and other adipokines, which indicates its possible role in modulating the adipokine secretions in adipose tissues.